Determination of the effect of iatrogenic blood contamination on lactate dehydrogenase and creatine kinase activity in canine cerebrospinal fluid. (6th November 2022) - Brune, Jourdan E.; Chen, Annie V.; Coffey, Todd
Abstract: Background: Lactate dehydrogenase (LDH) and creatine kinase (CK) have differential tissue activity and isoenzyme profiles. LDH and CK exist as 5 and 3 isoenzymes, respectively, in both serum and cerebrospinal fluid (CSF). Studies have demonstrated that measuring LDH, CK, and their isoenzymes in CSF has diagnostic and prognostic values for dogs and people with neurologic disorders. Objectives: Iatrogenic blood contamination can distort the results of CSF analysis. The purpose of this study was to determine allowable thresholds of blood contamination (RBC/μL) for accurate measurement of LDH, CK, and their isoenzymes in canine CSF. Methods: Venous blood and CSF were collected from healthy dogs. Total LDH and CK activity were measured spectrophotometrically. Isoenzyme profiles were determined using gel electrophoresis and densitometric scanning. All samples were analyzed within 6 hours of collection. A nonlinear mixed effects regression model was used to estimate the allowable thresholds of blood contamination for accurate measurement of LDH, CK, and their isoenzymes in canine CSF. Results: The threshold of iatrogenic blood contamination for total LDH and total CK in healthy dogs are 6696 RBC/μL (95% CI 3879–11 187) and 5961 RBC/μL (95% CI 2939–12 085), respectively. LDH‐1 is the most sensitive isoenzyme to iatrogenic blood contamination, while LDH‐4 is the least sensitive. Conclusions: These results are important for the interpretation of LDH, CK, and their isoenzymes in canine CSF. Additionally, our methodology is translatable for determining thresholds of acceptable iatrogenic blood contamination in CSF for other diagnostic and prognostic biomarkers of neurologic disease.